USM EXPERT IN INSTRUCTIONAL TECHNOLOGY PRODUCES 21ST CENTURY INSTRUCTIONAL DESIGN MODEL - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 19 January 2016 – An expert in Instructional Technology at Universiti Sains Malaysia (USM) Professor Dr. Balakrishnan Muniandy, 60, along with Outstanding Educator Award recipient Dr. Ismail Zain are currently testing a newly-designed 21st century teaching model which is intended to be used in schools in the country.